Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find the sum of the values of the parameter $a$ such that for some non-constant polynomials with real coefficients $f(x)$ and $g(x)$,

$$g(x)^2 =f(x)^3−12 f(x)^2 + 45 f(x) − a$$

My understanding: Since $g(x)^2$ is always positive, $$f(x)^3−12f(x)^2+45f(x)−a \geq0.$$

$f(x)^3−12f(x)^2+45f(x) \geq 0$ for $x \geq 0$ and $<0$ for $x<0$.Therefore, for $x\geq0$, $a \in (-\infty,0]$ and for $x<0$, $a > 0$.

Hence the sum should be zero, since $a$ can take all the possible values. Can anyone please tell me whether the above is correct or not?

share|cite|improve this question
If $a$ is fixed at the beginning, you can't let it move afterwards. Unless I did not understand the question. – 1015 Mar 6 '13 at 18:30
What values can $a$ take? Real, integer, ...? – vonbrand Mar 6 '13 at 20:49
it can take any value – user65368 Mar 6 '13 at 21:01
This is a problem posed by Brilliant, which provides weekly problems for students to work on. You may view it here - Solve this problem: Poly-polynomials. As the week is over, I'm fine with the posts being kept up. It does explain why there are repeat versions of this problem, and it will unlikely get accepted. - Calvin Lin Brilliant Challenge Master – Calvin Lin Mar 11 '13 at 20:08

Lemma For $\alpha_1, \alpha_2, \ldots, \alpha_n \in \mathbb{C}$ such that $\alpha_1 \ne \alpha_2 \ne \cdots \ne \alpha_n$ and $p(z), q(z)$ any two polynomials over $\mathbb{C}$: $$p(z)^2 = \prod_{i=1}^n(q(z)-\alpha_i) \implies p(z), q(z) \text{ constant }\tag{*}$$

(Proof) Assume the contrary, suppose there are two non-constant polynomials $p(z), q(z)$ such that $$p(z)^2 = \prod_{i=1}^n(q(z)-\alpha_i)$$ Since $\alpha_1, \alpha_2, \ldots, \alpha_n$ are all distinct, the set of roots for $q(z) - \alpha_i, i = 1,\ldots,n$ are disjoint from each other. Since the roots on L.H.S of $(*)$ appear in pairs and $\mathbb{C}[x]$ is an UFD. The roots of each $q(z) - \alpha_i$ also come in pairs. This means we can factor $p(z)$ into $n$ pieces such that:

$$p(z) = \prod_{i=1}^n p_i(z) \;\;\text{ and }\;\; p_i(z)^2 = q(z) - \alpha_i,\, i = 1,\ldots,n$$

Notice for $1 \le i \ne j \le n$, $$(p_i(z) + p_j(z))(p_i(z) - p_j(z)) = (q(z) - \alpha_i) - ( q(z) - \alpha_j ) = \alpha_j - \alpha_i \ne 0$$ are constants. This implies all $p_i(z)$ are constants. As a result, $p(z) = \prod_{i=1}^n p_i(z)$ and $q(z) = p_1(z)^2 + \alpha_1$ are also constants, a contradiction!

(Comment) In the general case when the multiplicity of some $\alpha_i$ is greater than $1$. A similar argument shows that in order for $$ p(z)^2 = \prod_{i=1}^n (q(z) - \alpha_i)^{m_i}$$ to have non-constant solutions, a necessary and sufficient condition is at most one of the multiplicity $m_i$ is odd. However, we don't need to use this piece of info for the original problem.

Back to original problem

Applying the lemma to the equation $$g(x)^2 = P(f(x)) = f(x)^3−12 f(x)^2 + 45 f(x) − a\tag{**}$$ In order for it to has non-constant solutions, a necessary condition is the cubic polynomial $P(z) = z^3 - 12z^2 + 45z - a$ has repeated roots. Let $c$ be any repeated root, $(z - c)^2$ will be a factor of $P(z)$ and hence $P'(c) = 3c^2 - 24 c + 45 = 3(c-3)(c-5) = 0 \implies c = 3 \text{ or } 5$.

Case c = 3

$P(3) = 0 \implies a = 54$ and $(**)$ reduces to $g^2 = P(f) = (f-6)(f-3)^2$.

If one assign $6,3,3$ to $\alpha_1,\alpha_2,\alpha_3$ and repeat the arguments in proof of lemma, we see $g(z)$ contains a factor $h(z)$ such that:

$$h(z)^2 = f(z) - 6 \implies g(z)^2 = P(f(z)) = h(z)^2(h(z)^2 + 6 - 3)^2$$

This implies $(**)$ has solutions of the form

$$\begin{align} f(z) &= h(z)^2 + 6\\ g(z) &= h(z)(h(z)^2 + 3) \end{align}$$

Case c = 5

$P(5) = 0 \implies a = 50$ and $(**)$ reduces to $g^2 = P(f) = (f-2)(f-5)^2$.

Once again $g(z)$ contains a factor $h(z)$ such that:

$$h(z)^2 = f(z) - 2 \implies g(z)^2 = P(f(z)) = h(z)^2(h(z)^2 + 2 - 5)^2$$

This implies $(**)$ has solutions of the form

$$\begin{align} f(z) &= h(z)^2 + 2\\ g(z) &= h(z)(h(z)^2 - 3) \end{align}$$

And the desired answer is $54 + 50 = 104$.

share|cite|improve this answer
And there's still no upvote...+1. – 1015 Mar 7 '13 at 20:57

This makes no sense: there's no reason that the sign of $f(x)^3 - 12 f(x)^2 + 45 f(x)$ should have anything to do with the sign of $x$.

In any case, you want $f(x)^3 - 12 f(x)^2 + 45 f(x) - a \ge 0$ for all $x$. That can only happen if $f$ is a polynomial of even degree.

As a matter of fact, if you want $f$ to be a quadratic polynomial (and thus $g$ cubic), you need $a = 50$ or $54$:

$$ \left( {x}^{2}+2 \right) ^{3}-12\, \left( {x}^{2}+2 \right) ^{2}+45\, \left({x}^{2}+2\right) - 50= \left( {x}^{3}-3\,x \right) ^{2} $$

$$\left( {x}^{2}+6 \right) ^{3}-12\, \left( {x}^{2}+6 \right) ^{2}+45\, \left({x}^{2}+6 \right) - 54= \left( {x}^{3}+3\,x \right) ^{2} $$

I don't know if there are solutions of higher degree.

EDIT: Let $P(z) = z^3 - 12 z^2 + 45 z - a$. Suppose $P(f(x)) = g(x)^2$, where $f$ and $g$ are nonconstant polynomials. If $g$ has degree $d$, then $f$ has degree $2d/3 < d$.

Differentiating the equation $P(f(x)) = g(x)^2$, we get $P'(f(x)) f'(x) = 2 g(x) g'(x)$. In particular, if $r$ is a (real or complex) root of $g(x)$, then either $P'(f(r)) = 0$ or $f'(r) = 0$. If $P'(f(r)) = 0$, then since the roots of $P'(z) = 3 z^2 - 24 z + 45 = 3 (z-3)(z-5)$ are $3$ and $5$, we have $f(r) = 3$ or $f(r) = 5$. Thus $P(3) = 0$ or $P(5) = 0$. But $P(3) = 54 - a$ and $P(5) = 50 - a$, so $a = 50$ or $54$.

Now it is possible that $f'(r) = 0$ for all roots $r$ of $g(x)$. But $f'$ has degree $< d - 1$, so there is at least one root $r$ which has higher multiplicity as a root of $g$ than it does as a root for $f'$. That is, for some $r$, $c \ne 0$ and positive integer $k$ we have $f(x) = f(r) + c (x-r)^{k} + O((x-r)^{k+1})$ while $g(x) = O((x-r)^{k})$. Then $$P(f(x)) = P'(f(r)) c (x-r)^k + O((x-r)^{k+1}) = g(x)^2 = O((x-r)^{k+1})$$ so again $P'(f(r)) = 0$.

share|cite|improve this answer
In fact, when $a=50, 54$, there are solutions of higher degree, but there are no solutions for all other $a$. I'll be posting an answer regarding this when I get home in a while. – Ivan Loh Mar 7 '13 at 8:01

It is easy to plot $P(x)=x^3-12x^2+45x$. (This can also be done manually, by looking at critical points) Looking at the behaviour of $P(x)$, we note that the cubic equation $P(x)=a$ has 1 real root and 2 distinct complex roots (conjugate pair) for $a<50, a>54$, 3 distinct real roots for $50<a<54$, and 2 real roots (with 1 repeated) for $a=50, 54$.

Consider $a \not =50, 54$. Then the cubic equation $P(x)=a$ has at least 1 real root $c$ and no repeated complex roots. Factorise $g(x)^2=P(f(x))-a=(f(x)-c)(f(x)^2+pf(x)+q)$, where $p, q \in \mathbb{R}$.

We show that $(f(x)-c)$ and $(f(x)^2+pf(x)+q)$ have no common complex root. Assume on the contrary that they have a common root $\alpha$, then $f(\alpha)$ is a common complex root of $x-c$ and $x^2+px+q$, so $f(\alpha)$ is a repeated complex root of $P(x)=a$, a contradiction.

Now each complex root in $g(x)^2$ has even multiplicity, so each complex root in $(f(x)^2+pf(x)+q)$ has even multiplicity. Since $(f(x)^2+pf(x)+q) \in \mathbb{R}[x]$ and $(f(x)^2+pf(x)+q)$ has positive leading coefficient, this implies that $(f(x)^2+pf(x)+q)=h(x)^2$ for some $h(x) \in \mathbb{R}[x]$. (To see why, note that the complex roots come in conjugate pairs, so that $(f(x)^2+pf(x)+q)$ is the product of squares of quadratics.)

Finally, observe that since $x^2+px+q$ has no repeated roots, we have $x^2+px+q=(x+\frac{p}{2})^2+r$, where $r \not =0, r \in \mathbb{R}$. Thus $h(x)^2=(f(x)^2+pf(x)+q)=(f(x)+\frac{p}{2})^2+r$, so $r=(h(x)-(f(x)+\frac{p}{2}))(h(x)+(f(x)+\frac{p}{2}))$, so both $(h(x)-(f(x)+\frac{p}{2}))$ and $(h(x)+(f(x)+\frac{p}{2}))$ are constant, so that $f(x)$ must be constant, a contradiction.

For $a=50$, factorise $g(x)^2=P(f(x))-50=(f(x)-2)(f(x)-5)^2$, so we have the general family of solutions $f(x)=q(x)^2+2, g(x)=q(x)(f(x)-5)$, where we restrict $q(x)$ to be nonconstant, since both $f(x), g(x)$ are nonconstant.

For $a=54$, factorise $g(x)^2=P(f(x))-54=(f(x)-6)(f(x)-3)^2$, so we have the general family of solutions $f(x)=q(x)^2+6, g(x)=q(x)(f(x)-3)$, where we restrict $q(x)$ to be nonconstant, since both $f(x), g(x)$ are nonconstant.

Edit: Forgot to answer the question. To conclude, the sum of values of permissible $a$ is $50+54=104$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.